Sex, race and Romanticism: The meta-vampire in emo fandom. (1st September 2021) - Fathallah, Judith
The genealogy stretching from Romanticism to the tortured poets of the emotional hardcore music scene is by now well established. Emotional hardcore, or emo, is invested in the construction of the usually White male artist, a sensitive and creative being subject to a great deal of suffering ‐ as a result both of his artistic nature and of the external forces aligned against him. The European Romantics invented the concept of artist as cultural icon ‐ Lord Byron is often considered Britain's first celebrity. He was also, not coincidentally, Britain's first literary vampire. This article utilizes a discursive analysis based in open coding to consider emo fandom's obsession with the figure of the vampire, especially what emo fans ‐ who are mostly girls ‐ have done with it in fanfic. Considering the gendered genealogy of the vampire, and the problematic gender politics of the emo scene, I explore how the constraints and opportunities of these discursive structures influence the ways emo fans imagine vampires, who appear so often in their writing. Picking out key themes of sex, race and the ethics of the vampire inherited from both emo fandom and vampire literature generally, I argue that the selected sample demonstrates a transformative impulse towards race and sex, which is ultimately still contained by the overarching discursive structures within which artists operate.